GETTING READY FOR EARTHQUAKE DISASTER WITH TABLETOP EXERCISE FOR DISASTER MANAGEMENT - Ikhda Ulya; Bintari Ratih Kusumaningrum; Ika Setyo Rini (Journal of Nursing Science Update (JNSU), 2020)
Disaster is an event that can destruct the community living. Malang is a city which have an active seismic, that have high potential of earthquake. To reduce the risk or effect of disaster we need tabletop exercise for disaster management as a mitigation activity. The purpose of this study was to knowing the effect of tabletop exercise on staff readiness once deal with earthquake disaster. This study was quasy experimental with purposivesampling technique. We obtained 24 respondents from administrative staff of medical Faculty Universitas Brawijaya. They were devided into intervention group (n=12) dan control group (n=12). The readiness was measured with knowledge and attitude score pre and post table top exercise. Wilcoxon signed rank test showed that there were significant differences between score pre and post test of knowledge about disaster management in control group (p value= 0.033) and in intervention group (p value=0.005). Dependent Ttest showed that there were significant effect on attitude pre and post table top exercise for disaster management simulation (p value =0,001), but no significant effect in control group (p value =0.376). Independent T-test for attitude and mann whitney test showed that there is no difference between intervention and control group in attitude (p value= 0.318) and knowledge (p value =0.680). In conclusion there is significant effect of tabletop exercise to readiness of the staff medical faculty Universitas Brawijaya once deal withearthquake disaster. But there is no difference in both method of education